Pairalisme i identitat al segle XIX català: una construcció des de la imaginació literària - Anna Llovera Juncà (Catalonia)
This article proposes an exploration of the mythic and imaginary background of the Catalan rural novels in the second half of the 19th century, in which the pairalisme lesson has a determinant role. In these texts, the farmer, a not very present figure in literature until then, is invested with the catalanism essence, and the world where he belongs, the rural one, is transformed into the only possible habitat for the «good Catalan».